2004
DOI: 10.1016/j.ehj.2004.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Presence of sympathetically denervated but viable myocardium and its electrophysiologic correlates after early revascularised, acute myocardial infarction

Abstract: After early reperfusion for myocardial infarction, viable but denervated myocardium is frequent and correlates with slow depolarisation and repolarisation. However, in patients with small infarct size and preserved left ventricular function, these findings seem to have little influence on outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
72
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 25 publications
5
72
0
Order By: Relevance
“…78 The extent or severity of autonomic defects predicted VT inducibility 79 and occurrence of an ICD discharge or SCD. 80 PET tracers such as 11C-hydroxyephedrine (11-CHED) improve the signal-noise ratio allowing better quantification.…”
Section: Sympathetic Activitymentioning
confidence: 99%
“…78 The extent or severity of autonomic defects predicted VT inducibility 79 and occurrence of an ICD discharge or SCD. 80 PET tracers such as 11C-hydroxyephedrine (11-CHED) improve the signal-noise ratio allowing better quantification.…”
Section: Sympathetic Activitymentioning
confidence: 99%
“…The rationale for SPECT is that the presence of regional autonomic tracer defects, particularly if tracer uptake is relatively preserved on a separately obtained standard rest perfusion image, i.e., an autonomic/perfusion mismatch, may indicate potential for electrical heterogeneity and denervation supersensitivity, pre-disposing to potentially lethal arrhythmias. 56,57 While there is no officially established method for scoring SPECT 123 I-mIBG images, analysis can be performed similar to the conventional 17-segment method used for MPI, with generation of a summed score. 37,58 However, a key difference for 123 I-mIBG images is that when there is globally decreased uptake, homogeneous tracer uptake cannot be scored as normal as, unlike the custom for perfusion images, one cannot assume a ''normal'' region.…”
Section: Image Analysis and Interpretationmentioning
confidence: 99%
“…56,[134][135][136][137] Injury to sympathetic innervation may persist after myocyte recovery, resulting in areas of autonomic/perfusion mismatch, possibly pre-disposing to post-MI arrhythmias. 57,[138][139][140] Tomoda et al 141 showed that 3-4 weeks after nonST segment elevation MI, 123 I-mIBG defects may be present without Tl-201 perfusion defects. 123 I-mIBG defects can occur following angina, 142 and may be present up to 6 months after coronary spasm.…”
mentioning
confidence: 99%
“…For example, simultaneously investigating myocardial sympathetic innervation and perfusion/ viability may help in the identification of the pro-arrhythmic, denervated but viable infarct borderzone [13,14]. Alternatively, very specific insights may be provided by combining information on myocardial sympathetic activity and various agents identifying, for example apoptosis, extracellular matrix activation, or angiogenesis [15].…”
mentioning
confidence: 99%